2010
DOI: 10.1007/s10533-010-9480-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of dissolved organic matter in Parisian urban aquatic systems: predominance of hydrophilic and proteinaceous structures

Abstract: Understanding the nature of organic matter is a necessary first step in assessing contaminant bioavailability and allowing water supply managers to optimise the treatment train in the aim of providing safe and inexpensive drinking water. This study provides further insight into the composition, structure and functional groups of dissolved organic matter (DOM) (both hydrophobic and hydrophilic) from urban aquatic systems by means of various analytical techniques (DAX-8/XAD-4 fractionation, elemental analysis, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 81 publications
1
23
0
1
Order By: Relevance
“…34,35 Conversely, higher SUVA 254 values have been observed for humic material isolated from high DOC/highly colored surface waters (e.g., 4.0 and 4.8 for Gartempe River and Suwannee River NOM, respectively). 19 This moderate WW humic SUVA 254 value would indicate a different aromatic character as compared to River humic.…”
Section: Acs Paragon Plus Environment Langmuirmentioning
confidence: 99%
“…34,35 Conversely, higher SUVA 254 values have been observed for humic material isolated from high DOC/highly colored surface waters (e.g., 4.0 and 4.8 for Gartempe River and Suwannee River NOM, respectively). 19 This moderate WW humic SUVA 254 value would indicate a different aromatic character as compared to River humic.…”
Section: Acs Paragon Plus Environment Langmuirmentioning
confidence: 99%
“…The second peak, on the other hand, shows that there are C=O aromatic bonds seen in the 1640-1550 cm−1 bandwidth [16,17]. It was observed that the aromatic structure observed in this band stem from structures like cyclic and alicyclic compounds that have low wave numbers, ketones and aromatic carboxylic acids [18,19]. According to these results, it is observed that there are some changes, although little, in the peak values with membrane, ozone and ozone+membrane treatments.…”
Section: E Atr-ftir Spectramentioning
confidence: 83%
“…The 3400-3300 cm−1 peak shows the O-H stretching bonds [16,17]. This peak stems from the humic matters like alcohols, phenols and carboxylic acids that are frequently observed in water [18]. The second peak, on the other hand, shows that there are C=O aromatic bonds seen in the 1640-1550 cm−1 bandwidth [16,17].…”
Section: E Atr-ftir Spectramentioning
confidence: 98%
“…These anthropogenic inputs modify the nature of dissolved organic matter (DOM). For example, OM in the treated effluent of waste-water displays a strong proteinaceous nature, which is interpreted as a result of the intense microbial activity during urban water treatment (Pernet-Coudrier et al 2011). Moreover, it has been shown that when compost is added to a soil, the hydrophobic compounds remain selectively on solid surfaces whereas more hydrophilic compounds are exported in solution (Jardine et al 1989, Kaiser et al 1996.…”
Section: Continental and Anthropogenic Sources Of Om In Aquatic Ecosymentioning
confidence: 99%